Quo Vadis The Integrating Islam and Science, A Comparative Study of the Thoughts of Al Faruqi, Al Attas, and Amin Abdullah: Quo Vadis Integrasi Islam dan Sains, Telaah Komparatif Pemikiran Al Faruqi, Al Attas, dan Amin Abdullah - Permadi, Muhammad Syafrani; Fahmi, Muhammad; Muluk, M.Islah Azharul; Dhuha, Moch. Chafid (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The dichotomy between religious and modern sciences, rooted in colonial legacies, has long shaped fragmented educational paradigms within the Muslim world. Specific Background: This separation has produced graduates with compartmentalized competencies, limiting the holistic development of knowledge within Islamic education. Knowledge Gap: While various scholars have proposed frameworks to integrate Islam and science, comparative analyses of their epistemological foundations remain limited. Aims: This study aims to analyze and compare the concepts of Islamic-scientific integration proposed by Ismail Raji al-Faruqi, Syed Muhammad Naquib al-Attas, and M. Amin Abdullah. Results: Through a library research method and content analysis, the study reveals that al-Faruqi emphasizes the Islamization of knowledge based on tawhid, al-Attas promotes the purification of knowledge through adab, and M. Amin Abdullah advances an integration-interconnection model addressing contemporary challenges. Novelty: This study provides a comparative synthesis that clarifies the theoretical trajectories and philosophical underpinnings of each approach. Implications: The findings contribute to developing a more holistic and integrative framework for Islamic higher education, fostering the unification of faith and reason toward comprehensive human development within the Islamic worldview. Highlights: Highlights comparative insights from Al-Faruqi, Al-Attas, and M. Amin Abdullah. Emphasizes holistic integration of Islamic and modern sciences. Offers a transformative framework for Islamic higher education. Keywords: Islamization of Knowledge, Integration of Science and Religion, Interconnected Paradigm